Mining Waste Challenges: Environmental Risks of Gigatons of Mud, Dust and Sediment in Megadiverse Regions in Brazil - Carmo, Flávio F.; Lanchotti, Andressa O.; Kamino, Luciana H.Y. (Sustainability, 2020)
The management of long-lived mining wastes is a complex environmental challenge, but the subject is little discussed among the public, scientific community, and policymakers. The negative environmental impacts caused by mining wastes are severe and cause damage to human health and the loss and degradation of natural ecosystems. With the objective of stimulating discussion to advance the development of measures to contain threats to biodiversity and to mitigate negative impacts, we present an overview of total volumes of mining waste disposal in tailings dams and dump piles, discriminating them by ore type and biome. We highlight the major environmental risks and challenges associated with tropical forests, savannas, and freshwater ecosystems and possible limitations and advances in public policies and governance. The scale of this challenge is global, as some data show, for example, Brazil generated 3.6 billion tons of solid mining waste in dump piles in the period between 2008 and 2019. The volume is equivalent to 62% of the global mass of nonfuel minerals removed from the planet’s crust in 2006. Numerous socio-environmental disasters are caused by catastrophic mining dam failures, and over the last 34 years, an average of one failure has occurred every three years in Brazil.